Euphoria a novel - King, Lily (2014)
"English anthropologist Andrew Bankson has been alone in the field for several years, studying a tribe on the Sepik River in the Territory of New Guinea with little success. Increasingly frustrated and isolated by his research, Bankson is on the verge of suicide when he encounters the famous and controversial Nell Stone and her wry, mercurial Australian husband Fen. Bankson is enthralled by the magnetic couple whose eager attentions pull him back from the brink of despair. Nell and Fen have their own reasons for befriending Bankson. Emotionally and physically raw from studying the bloodthirsty Mumbanyo tribe, the couple is hungry for a new discovery. But when Bankson leads them to the artistic, female-dominated Tam, he ignites an intellectual and emotional firestorm between the three of them that burns out of anyone's control."--Dust jacket.
Map on end papers.
Kirkus Prize, Fiction, 2014
National Book Critics Circle Award, Finalist, 2014
New England Book Award, Fiction, 2014
Keywords: Anthropologists -- New Guinea -- Fiction; Nineteen thirties -- Fiction; Married people -- Fiction; Triangles (Interpersonal relations) -- Fiction; New Guinea -- Fiction; Historical fiction